Reticulocytes: Plasmodium vivax target cells (2013)
Reticulocytes represent the main invasion target for Plasmodium vivax, the second most prevalent parasite species around the world causing malaria in humans. In spite of these cells' importance in research into malaria, biological knowledge related to the nature of the host has been limited, given the technical difficulties present in working with them in the laboratory. Poor reticulocyte recovery from total blood, by different techniques, has hampered continuous in vitro P. vivax cultures being developed, thereby delaying basic investigation in this parasite species. Intense research during the last few years has led to advances being made in developing methodologies orientated towards obtaining enriched reticulocytes from differing sources, thereby providing invaluable information for developing new strategies aimed at preventing infection caused by malaria. This review describes the most recent studies related to obtaining reticulocytes and discusses approaches which could contribute towards knowledge regarding molecular interactions between target cell proteins and their main infective agent, P. vivax. © 2013 Société Française des Microscopies and Société de Biologie Cellulaire de France.